Diseño de un prototipo software para la administración de Historias Laborales - Garzón Vela, Luis Enrique
The project aims at the design (technical and functional) of a software prototype for the management of employment histories of active personnel of the SENA Regional Cauca. Although, the Project was done for Centro de comercio y Servicios, It could be possible to use the software in all SENA.   The project is based on an existing need to manage employment histories, digitize them and facilitate the generation of a certificate.   The project began with a phase of gathering information with the interested area of the process, that is, human resources. This collection of information allowed to know in detail the functional need and from it, define the technical scale of the prototype. Besides, it analyzed all  the regulations associated with the process, in order to contemplate legal requirements.   Once the requirements were identified, the design phase was raised, in which the cases of use of the system and the proposals for the required interface were modeled and the development process took place based on some elements of agile methodologies such as they are: Scrum and Xp, which allowed to have a functional prototype that allows to fulfill the scope described previously.   To conclude the exercise, a phase of technical and functional tests is defined that allow the evaluation of the conformity of the system versus the requirements and needs identified in previous phases. From these tests, evaluation reports are generated that will allow generating functional improvements to the system, bug solutions and optimizations that may occur in the process. In addition, and as a feedback exercise, the process will generate a report with the lessons learned from the process. Whereby the general basis for the development of a new phase in which the prototype can be more usable.